A Smartphone‐Enabled Portable Digital Light Processing 3D Printer. Issue 35 (18th July 2021) - Li, Wanlu; Wang, Mian; Mille, Luis Santiago; Robledo Lara, Juan Antonio; Huerta, Valentín; Uribe Velázquez, Tlalli; Cheng, Feng; Li, Hongbin; Gong, Jiaxing; Ching, Terry; Murphy, Caroline A.; Lesha, Ami; et al.
Abstract: 3D printing has emerged as an enabling approach in a variety of different fields. However, the bulk volume of printing systems limits the expansion of their applications. In this study, a portable 3D Digital Light Processing (DLP) printer is built based on a smartphone‐powered projector and a custom‐written smartphone‐operated app. Constructs with detailed surface architectures, porous features, or hollow structures, as well as sophisticated tissue analogs, are successfully printed using this platform, by utilizing commercial resins as well as a range of hydrogel‐based inks, including poly(ethylene glycol)‐diacrylate, gelatin methacryloyl, or allylated gelatin. Moreover, due to the portability of the unique DLP printer, medical implants can be fabricated for point‐of‐care usage, and cell‐laden tissues can be produced in situ, achieving a new milestone for mobile‐health technologies. Additionally, the all‐in‐one printing system described herein enables the integration of the 3D scanning smartphone app to obtain object‐derived 3D digital models for subsequent printing. Along with further developments, this portable, modular, and easy‐to‐use smartphone‐enabled DLP printer is anticipated to secure exciting opportunities for applications in resource‐limited and point‐of‐care settings not only in biomedicine but also for home and educational purposes. Abstract : A smartphone‐enabled Digital Light Processing (DLP) 3D printer based on a smartphone‐powered projector and a customized touchscreen smartphone app is developed, featuring portability, modularity, and an easy‐to‐use interface. The ability of printing with versatile materials covers commercial resins and several hydrogel‐based (bio)inks. This platform is proven to be applicable to fabrication of medical implants, in situ bioprinting, and integration with a 3D object‐scanning app.